Tourism Development in Soppeng Regency: Analysis of the Role of the Tourism Office in the Development of Ompo Natural Tourism - Evan Gunawan; Herlina Sakawati; Sulmiah; Anisa Fitri (Perkembangan Kajian Sosial, 2024)
This study aims to find out the role of the Tourism Office in Developing Ompo Nature Tourism in Soppeng Regency. This study uses a descriptive qualitative approach. Data collection was carried out using observation techniques, interviews, and documentation. The data obtained from the results of this study were processed using interactive model analysis, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the role of the Paratourism Office in Developing Ompo Nature Tourism in Soppeng Regency has not been maximized. This is based on the existence of 3 role indicators, namely Motivator, Facilitator, and Dynamizer. These three indicators cannot be said to have not gone well. The Tourism Office has not carried out its role well as a motivator because of the lack of employee activity in carrying out its duties and functions as well as the lack of encouragement or even pressure that can move employees for how tourism in Soppeng district can progress and develop with the characteristics and uniqueness of different natural tourism. The role of the Tourism Office, which has not carried out its role properly as a facilitator, is seen from the facilities provided is inadequate. The dynamator has not done its role well, judging from the lack of significant development carried out by the Tourism Office to attract tourists to visit the ompo natural tourism.